Dysregulation of the Cytokine GM-CSF Induces Spontaneous Phagocyte Invasion and Immunopathology in the Central Nervous System - Spath, Sabine; Komuczki, Juliana; Hermann, Mario; Pelczar, Pawel; Mair, Florian; Schreiner, Bettina; Becher, Burkhard (Immunity (Cambridge, Mass.), 2017)
Chronic inflammatory diseases are influenced by dysregulation of cytokines. Among them, granulocyte macrophage colony stimulating factor (GM-CSF) is crucial for the pathogenic function of T cells in preclinical models of autoimmunity. To study the impact of dysregulated GM-CSF expression in vivo, we generated a transgenic mouse line allowing the induction of GM-CSF expression in mature, peripheral helper T (Th) cells. Antigen-independent GM-CSF release led to the invasion of inflammatory myeloid cells into the central nervous system (CNS), which was accompanied by the spontaneous development of severe neurological deficits. CNS-invading phagocytes produced reactive oxygen species and exhibited a distinct genetic signature compared to myeloid cells invading other organs. We propose that the CNS is particularly vulnerable to the attack of monocyte-derived phagocytes and that the effector functions of GM-CSF-expanded myeloid cells are in turn guided by the tissue microenvironment.